The prevalence of functional gastrointestinal disorders related symptoms and the association with working place among healthcare workers who were in the fighting against COVID-19 in regional China - Zhang, Yan; Guan, Yue; Shen, Ya; Qiao, Huifen; Yuan, Jie; Xu, Fei (Frontiers in Public Health, 2022)
Objectives To investigate the prevalence of functional gastrointestinal disorders (FGIDs) related symptoms among healthcare workers (HWs) who were in the fighting against COVID-19 in Nanjing of China, and further to examine the association between working place and FGIDs-related symptoms among HWs during the period of COVID-19 epidemic. Methods An online anonymous survey was conducted among those HWs without history of FGIDs, who took part in the fighting against the COVID-19 epidemic between July and September of 2021 in Nanjing, China. All the 15 FGIDs-related symptoms listed included in the Rome IV diagnostic questionnaire for adults were included investigated in this study. The outcome variable was the presence of FGIDs-related symptoms (“Yes” or “No”), while the independent measure was participants’ working place (“in-ward” or “out-ward”). Logistics regression models were applied to calculate odds ratios (ORs) and 95% confidence intervals (CIs) to assess the association of working place with FGIDs-related symptoms among those healthcare workers. Results Totally, 336 eligible participants completed the survey. The prevalence of FGIDs-related symptoms was 48.8% (95%CI=43.4%, 54.3%) among overall participants, with 40.7% (95%CI = 33.14%, 48.71%) and 56.3% (95%CI = 48.59%, 63.73%) for in-ward and out-ward HWs, respectively. Compared to their in-ward counterparts, those out-ward HWs were at a 1.88-fold likelihood (95%CI=1.22, 2.89) to experience FGIDs-related symptoms during the period of fighting against the COVID-19 epidemic. After adjustment for potential confounders, such a positive association attenuated but still remained significant. Conclusions A high prevalence of FGIDs-related symptoms was observed among those HWs who were without history of FGIDs during the fighting against COVID-19, and out-ward HWs were at a significantly higher risk to experience FGIDs-related symptoms relative to their in-ward counterparts in regional China. It has important implications that particular attention shall be paid to functional gastrointestinal issues for healthcare workers, especially those who are at uncertain risks of infectious diseases, when they participate in response to public health emergencies in future.